Sebagai PODCAST (POTENSI BIDARA (Ziziphus mauritiana L) TANAMAN ISTIMEWA SEBAGAI PENGGEMPUR COVID-19 ): Bidara sebagai penggempur COVID-19 - Irma Nurul Hermawati (JURNAL KESEHATAN : JURNAL ILMU- ILMU KEPERAWATAN, KEBIDANAN, FARMASI DAN ANALIS KESEHATAN, SEKOLAH TINGGI KESEHATAN MUHAMMADIYAH CIAMIS, 2022)
The emergence of this corona virus has shocked the world, the speed of its spread has made covid a global pandemic, not only Wuhan, other countries are also affected by this outbreak. Common symptoms that will be experienced if exposed to Covid are fever, cough, fatigue, and anosmia. One of the herbal plants that have many benefits for the health of the human body is the bidara plant. The efficacy of bidara leaves (Ziziphus mauritiana Lamk) has been mentioned in the Qur'an and the Hadith of the Prophet Muhammad SAW. In addition, there is a lot of archaeological evidence that humans use plant medicines for a better life, reducing disease and improving the quality of life. This study aims to determine the various benefits of bidara plants, especially in pandemic conditions, the reason for choosing this bidara plant is because it has various health benefits. The method used is the Systematic Literature Review (SLR) method, which is derived from the analysis and synthesis of various related references. The results obtained from the literature search results obtained 10 articles and scientific papers regarding the various benefits of bidara leaves. The biggest benefit of bidara leaves is as an antimicrobial, as well as other benefits contained in bidara leaves are antipyretic and anti-inflammatory analgesics, antioxidants, and immunomodulators. If we look at the analysis of the data regarding the benefits of the bidara plant (Ziziphus Mauritiana L), it can be concluded that this bidara can be used as a natural medicine to fight COVID-19.